Engagement in Digital Mental Health Interventions: Can Monetary Incentives Help? - Boucher, Eliane M.; Ward, Haley E.; Mounts, Amelia C.; Parks, Acacia C. (Frontiers in Psychology, 2021)
Digital mental health interventions are scalable and cost-effective strategies for increasing access to mental health care; however, dropout rates associated with digital interventions are high, particularly for open-access digital interventions. While some studies have focused on the predictors of dropout from digital mental health programs, few studies have focused on engagement features that might improve engagement. In this perspective paper, we discuss whether monetary incentives are one avenue to increasing user engagement in digital mental health programs. We begin by reviewing the literature on the effects of monetary incentives for behavior change in health domains (e.g., dietary behaviors, substance use, medication adherence). Then, drawing on a pilot study we conducted to test the effects of different levels of monetary incentives on usage and improvement in subjective well-being among users of a digital mental health program (Happify), we discuss the potential applications of monetary incentives for digital mental health interventions, the potential drawbacks of financial incentives in this context, and open questions for future research.